How can we strengthen the quadriceps femoris in patients with patellofemoral pain syndrome? - Kaya, Defne (CIC Edizioni Internazionali, 2012)
PURPOSE: the aim of this article was to review the clinical approach of quadriceps strengthening programmes. METHODS: a literature search was carried out from 1980 up to September 2011. Eligible studies were those that: (1) evaluated the patients with patellofemoral pain syndrome (not healthy or asymptomatic subjects) (2) examined the effect of kinetic chain exercises (3) examined the effect of weight-bearing exercises (4) compared the effect of the combined exercises programme in the treatment of patients with patellofemoral pain syndrome. RESULTS AND CONCLUSION: patients with patellofemoral pain syndrome may tolerate a closed kinetic chain exercises programme better than open kinetic chain. Weight-bearing and non-weight-bearing quadriceps exercises can significantly improve subjective and clinical outcomes in patients with patellofemoral pain syndrome. Combining treatments as an initial approach to treating patellofemoral pain but developing individualized more functional, global treatments are essential.